The Prevalence of Helicobacter pylori Positive Non-Cardia Gastric Adenocarcinoma is Low and Decreasing in a United States Population - Nguyen, Theresa H. (Dig Dis Sci, 2019)
BACKGROUND: Helicobacter pylori infection is an established causal factor for non-cardia gastric cancer. H. pylori negative gastric cancer prevalence among U.S. patients is unclear. METHODS: This retrospective cohort study examined H. pylori prevalence among consecutive patients with incident non-cardia gastric adenocarcinoma at the Houston VA Hospital (11/2007–10/2018). H. pylori positivity was defined by H. pylori on histopathology, positive antibody serology, stool antigen, or urea breath testing. We examined for trends in H. pylori negative gastric cancer based on year of diagnosis. Associations between histopathologic and cancer-related outcomes with H. pylori positivity were determined using regression models. RESULTS: Of 91 patients with gastric adenocarcinoma, most were men (N=87, 95.6%), black (N=47, 51.6%), with mean age at diagnosis of 68.0 years (SD 10.8). In addition to gastric cancer biopsy histopathology, 74 patients (81.3%) had ≥1 testing for H. pylori, including antibody serology (n=34), non-cancer gastric biopsy histopathology (n=63), or stool antigen (n=1). The overall prevalence of H. pylori infection was 38.5% and 45.9% among patients with ≥2 H. pylori tests. The proportions of H. pylori positive gastric cancer decreased from 50.0% (2007–2010) to 43.4% (2011–2014) and 29.3% (2015–2018) (p=0.096). Active/acute gastritis (adjOR 3.74), atrophic gastritis (adjOR 15.30), and gastric intestinal metaplasia (adjOR 3.65) were associated with H. pylori positive gastric cancer. DISCUSSION: The prevalence of H. pylori infection among patients with non-cardia gastric adenocarcinoma is relatively low (38.5–45.9%) and decreasing over time. This finding suggests there may be other important causal factors apart from H. pylori for gastric adenocarcinoma.